Procedural Failures as Independent Predictors of Delayed Intracranial Foreign Body Diagnosis in Mild Traumatic Brain Injury: A Multivariable Logistic Regression Analysis from North Sumatra, Indonesia - Aisyah Andina Rasyid; Priscilla Kapoor; Febria Suryani (Sriwijaya Journal of Forensic and Medicolegal, 2025)
Introduction: Retained intracranial foreign bodies in patients presenting with a Glasgow Coma Scale (GCS) score of 15 represent a rare but potentially fatal diagnostic pitfall in emergency trauma management, carrying profound medicolegal consequences under Indonesian health legislation. This retrospective multi-centre cohort study identified independent procedural risk factors predicting delayed diagnosis (>24 hours) of intracranial foreign bodies among mild traumatic brain injury (mTBI) patients in North Sumatra, Indonesia. Methods: Medical records from 1,240 mTBI patients (GCS 13–15) presenting to three tertiary trauma centres were reviewed; 45 cases with confirmed intracranial foreign bodies were identified, of whom 14 (31.1%) experienced delayed diagnosis. Results: Bivariate analyses demonstrated that failure to perform digital wound palpation (78.6% vs. 9.7%, p<0.001) and non-adherence to neuroimaging guidelines (71.4% vs. 9.7%, p<0.001) were significantly overrepresented in the delayed group. Multivariable logistic regression, adjusted for age, sex, mechanism of injury, and centre, identified non-adherence to computed tomography guidelines (adjusted odds ratio [aOR] 8.71, 95% CI 3.80–21.45, p<0.001), failure to palpate the wound bed (aOR 6.42, 95% CI 2.15–18.50, p<0.001), and an initial GCS of 15 (aOR 3.15, 95% CI 1.42–7.21, p=0.012) as significant independent predictors. Model calibration was excellent (Hosmer–Lemeshow p=0.711; accuracy 88.4%). Conclusion: A sentinel autopsy case demonstrated the fatal sequence: an undetected stone caused subarachnoid haemorrhage, brainstem compression, and asphyxial death. Strict protocol enforcement for secondary physical survey completion and CT guideline adherence is imperative to prevent fatal outcomes and mitigate medicolegal liability in Indonesian emergency departments.